Government Strategies In Planning Mass Transportation Medan City - Izharsyah, Jehan Ridho; Lubis, Faizal Hamzah Lubis (CV. Publikasi Indonesia, 2021)
Mass Transportation is the most important .The city of Medan is one of the cities that is quite a lot inhabited by people who in their daily activities use mass transportation. Therefore, to be a commitment and consistency of good spatial planning as well as the meaning of transportation regulations, the Medan city government needs to develop a strategy so that mass transportation becomes a solution and alternative for the community in reducing congestion in the city of Medan. The purpose of this study is to find out how strategic the Medan City Government is in planning mass transportation in Medan City. The method used in this study is a mix Methode approach with SWOT data analysis techniques and Analytical Hierarchy Processs (AHP). The results with the SWOT Quadrant I scoring 3.01, the main strategies that are carried out are: Strengthening environmental-based Transportation. Weighting with AHP, the online-based taxi mass transportation mode with 0.6898 or 68%, for example taxis, namely the Deli Trans Bus which is environmentally friendly, payment using SMART CARD.